Behavioral therapies in headache: focus on mindfulness and cognitive behavioral therapy in children and adolescents. (2nd December 2019) - Faedda, Noemi; Natalucci, Giulia; Baglioni, Valentina; Giannotti, Flavia; Cerutti, Rita; Guidetti, Vincenzo
ABSTRACT: Introduction : A wide proportion of children and adolescents with headache tends not to respond to various pharmacological treatments in use. The failure to respond to symptomatic treatment and prophylaxis is often due to the presence of a comorbid psychopathology undiagnosed or not properly treated. For these reasons and for the negative impact of headache on the quality of life of the patients and on the costs for the public health system, the adoption of an integrated multi-disciplinary perspective in the diagnosis and treatment of headache is needed. Areas covered : Several researchers have shown that behavioral treatment is effective as pharmacological treatment, not only for headache management but also to maintain a lifetime response to the headache treatment. In particular, Cognitive Behavioral Therapy (CBT) and Mindfulness have proven to be very resolutive both in the management of pain and in the management of stressful situations that can trigger the headache in children and adolescents with headache. Expert opinion : Although studies on behavioral treatments on children and adolescents with primary headaches are still few but a combined approach seems to be very useful in improving the quality of life of these subjects, especially in those who have internalizing disorders in comorbidities.